Research Scholar, Jagannath University, Jaipur (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
Productivity is a ratio of monetary value of  output to the monetary value of input. Higher  the productivity ratio of a company denotes  more efficiently the company has used its  resources. In the present research, an attempt  has been made to measure, analyse and compare  productivity of four companies of IT sector  during the period from 2010-11 to 2017-18  i.e. for eight years.  Intra-company comparison has been drawn with  the help of chi-square test and results indicate  that null hypothesis is accepted in all the cases  of IT companies. Inter-company comparison  has been drawn with the help of Kruskal Wallis  One Way ANOVA Test and results indicate that  null hypothesis is rejected.  After analysing the average overall productivity  it is observed that overall productivity is almost  one that means IT sector companies are not  optimally utilizing its resources, it is just meeting  its cost. It is recommended that the companies  should take steps to maintain the productivity  ratio high in future by optimally utilizing the  resources.
Keywords: Overall Productivity; Investor Input; Average Investment; Kruskal Wallis One Way ANOVA Test